Management accounting change in the Portuguese telecommunications industry - Major, M. (Global Advanced Research Journal of Management and Business Studies, 2012)
This paper sought to study the reasons that explain why has a telecommunications operator (called Marconi) changed its traditional management accounting systems (MAS) and replaced it with activity-based costing (ABC). The paper relied on qualitative data collected through a longitudinal and in-depth case study in the telecommunications sector. The investigation was informed by new institutional sociology (NIS) insights. The study evidenced that Marconi adopted ABC in order to fulfil its constituencies’ expectations of efficiency created with the reorganisation of the Portuguese telecommunications sector and the introduction of competition in the market. Furthermore, the paper contests the managerial emphasis that ABC has been subject to and claims that social accounting theories, such as institutionalism, should be adopted by management accounting researchers in order to achieve a deeper understanding of the ‘ABC phenomenon’.